Development of Folding Seats (Comfort, Easy, and Safety) During Use - Fadhila Lady Sifredy; Nur Isnaini (Proceedings Series on Health & Medical Sciences, 2021)
The elderly in carrying out activities both indoors and outdoors will experience difficulties due to their declining physical condition. Therefore, they will need extra time and effort and tend to tire easily and feel sore when doing various activities (such as sitting, walking, or standing for too long). It is necessary to produce a product that can help and make the elderly more comfortable in carrying out activities. Designing and developing a folding seat for the feasibility and comfort and safety of the seat mat. Tried the use of a folding seat mat. This research is a Research and Development (R&D) research. The sampling technique is purposive sampling with a total of 5 elderly people. The research instrument used a questionnaire. Data analysis using frequency distribution test. Research results Characteristics of respondents have an average age of 66.4 years with the youngest age 61 years and the oldest age is 70 years. The comfort level of using the Elderly Sitting Mat has an average comfort level of 33.8. The model or display of the seat used has a length of 150 cm and a width of 50 cm. This seat mat is equipped with safety on the right and left with a length of 35 cm, and there are recesses to adjust the angle of the backrest so that it can be adjusted as needed. This folding seat mat can be folded for easy storage. The level of comfort for the elderly when using the Folding Seat is in the very good category The comfort level of using the Elderly Sitting Mat has an average comfort level of 33.8. The model or display of the seat used has a length of 150 cm and a width of 50 cm. This seat mat is equipped with safety on the right and left with a length of 35 cm, and there are recesses to adjust the angle of the backrest so that it can be adjusted as needed. This folding seat mat can be folded for easy storage. The level of comfort for the elderly when using the Folding Seat is in the very good category The comfort level of using the Elderly Sitting Mat has an average comfort level of 33.8. The model or display of the seat used has a length of 150 cm and a width of 50 cm. This seat mat is equipped with safety on the right and left with a length of 35 cm, and there are recesses to adjust the angle of the backrest so that it can be adjusted as needed. This folding seat mat can be folded for easy storage. The level of comfort for the elderly when using the Folding Seat is in the very good category This folding seat mat can be folded for easy storage. The level of comfort for the elderly when using the Folding Seat is in the very good category This folding seat mat can be folded for easy storage. The level of comfort for the elderly when using the Folding Seat is in the very good category.